2010
DOI: 10.1002/prot.22851
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐based prediction of protein–peptide specificity in rosetta

Abstract: Protein-peptide interactions mediate many of the connections in intracellular signaling networks. A generalized computational framework for atomically precise modeling of protein-peptide specificity may allow for predicting molecular interactions, anticipating the effects of drugs and genetic mutations, and redesigning molecules for new interactions. We have developed an extensible, general algorithm for structure-based prediction of protein-peptide specificity as part of the Rosetta molecular modeling package… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…The growth in the number of protein complexes with a determined 3D structure has facilitated the development of structural tools to predict SLiM specificities (Betel et al , 2007; Encinar et al , 2009; King and Bradley, 2010; Petsalaki et al , 2009; Stein and Aloy, 2010). The ADAN database (Encinar et al , 2009) utilizes the FoldX algorithm (Schymkowitz et al , 2005) to perform an assessment of the stability and affinity of peptide–domain complexes under in silico mutagenesis analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The growth in the number of protein complexes with a determined 3D structure has facilitated the development of structural tools to predict SLiM specificities (Betel et al , 2007; Encinar et al , 2009; King and Bradley, 2010; Petsalaki et al , 2009; Stein and Aloy, 2010). The ADAN database (Encinar et al , 2009) utilizes the FoldX algorithm (Schymkowitz et al , 2005) to perform an assessment of the stability and affinity of peptide–domain complexes under in silico mutagenesis analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Most PRD families, however, display significant diversity in how peptides interact with domains, which fundamentally limits this approach. In a recent effort to alleviate this problem, King et al [15] combined peptide docking and subsequent structure-based binding prediction using the Rosetta scoring function. Molecular Dynamics simulations of domain-peptide bound states have also been carried out, emphasizing the importance of dynamics and flexibility for understanding the molecular basis of peptide binding [23][25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our best performing protocol (FPD + IRM) included both flexible peptide docking and gradient-based minimization of the backbone, emphasizing the need for backbone flexibility in attaining the best possible predictions of affinity and specificity. Smith and Kortemme [26] and King and Bradley [27] both found that introducing backbone flexibility by using conformational ensembles as inputs improved specificity prediction. This can be achieved through ensemble generators such as backrub [42] or the use of NMR structures.…”
Section: Resultsmentioning
confidence: 99%